Manual Soft-Tissue Mobilization in the Management of Hypertrophic Burn Scars: A systematic Review - Joel, Mathews; Karishma, Chauhan; Jeffery, Samuel R (INTI International University, 2025)
Burn scars continue to be a prominent public health problem worldwide, and even in developed nations, survivors of such injuries often develop hypertrophic scars due to excessive collagen deposition, pain, pruritus, cosmetic issues, and limited mobility. This systematic review aimed to identify the effectiveness of soft tissue mobilization (STM) manual techniques in the treatment of hypertrophic scars in burn patients. An extensive search was performed in the electronic databases of the PubMed, Scopus, Google Scholar, and Cochrane Library for published literature from 2017 to the present using the search terms “burn,” “hypertrophic scar,” “massage,” “soft tissue mobilization,” and “manual therapy” using the Boolean algorithm. A total of 11 studies, following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-analyses, fulfilled the inclusion criteria and thus rendered the systematic literature review. The literature included consisted of randomized controlled trials, quasi-experiments, and systematic reviews of burn patients that utilized STM. There was a positive correlation of STM techniques such as circular massage, linear massage, Deep Tissue Massage, and Cross Friction in the STM approach to improved scar elasticity, thickness, pain, itching, and mobility in the included literature in comparison to conservative treatments. This systematic literature review shows that STM is a novel, non-invasive method of adjunct rehabilitation in patients suffering from post-burn scars in medicine.